2023
DOI: 10.1002/aoc.7250
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress of nanocatalyst in the synthesis of heterocyclic compounds by barbituric acids

Elnaz Safari,
Ahmad Poursattar Marjani,
Mohsen Sadrmohammadi

Abstract: Heterocycles and barbituric acid analogs are particularly used in developing and designing new drugs because of their versatile binding properties for different biotargets. They are present in many natural compounds, vitamins, drugs, and biologically active molecules such as anticancer, antibiotic, antidiabetic, anti‐inflammatory, antidepressant, anti‐HIV, antimicrobial, and insecticidal agents. Using co‐friendly techniques under nanocatalyst conditions drives the synthesis of these bioactive compounds toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 106 publications
(311 reference statements)
0
2
0
Order By: Relevance
“…Numerous techniques for synthesizing N-heterocycles have been presented in the literature. [26,27] Shin et al reported the synthesis of 1,2,3-triazoles in 2012 using 2.5 mol % β-cyclodextrin in water. In this click reaction between azides and various acetylenes, βcyclodextrin functions as an effective phase transfer catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous techniques for synthesizing N-heterocycles have been presented in the literature. [26,27] Shin et al reported the synthesis of 1,2,3-triazoles in 2012 using 2.5 mol % β-cyclodextrin in water. In this click reaction between azides and various acetylenes, βcyclodextrin functions as an effective phase transfer catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the creation of an innovative method for the synthesis of fused heterocyclic molecules was crucial to the advancement of pharmacological applications. Numerous techniques for synthesizing N ‐heterocycles have been presented in the literature [26,27] . Shin et al .…”
Section: Introductionmentioning
confidence: 99%